Nocardia asteroides sinusitis in a pediatric patient: Case report with 20 year follow-up and review of the literature. Issue 7 (July 2015) - Sorichetti, Brendan; Westerberg, Brian D.; Tan, Rusung; Kozak, Frederick K.
Abstract Nocardia Asteroides infection in a non-immunocompromised pediatric patient is extremely rare. We present a case of ethmoid sinusitis and orbital subperiosteal abscess caused by N. asteroides with a 20 year follow up and a review of the literature. N. asteroides was grown from intraoperative cultures for mycobacteria following surgical incision and drainage of the abscess. Postoperatively, the patient received a seven month course of trimethoprim-sulfamethozaxole and had no subsequent sequelae. Nocardia infections are common in immunocompromised patients. We present what we believe to be the first case of pediatric Nocardia sinusitis with 20-year follow up.